The potential impact of COVID-19 infection on tuberculosis: a literature review - Akhtar, Muhammad Mahmood; Alotaibi, Saud Talaq; Althubeti, Abdullah Fayez; Alharthi, Shaker Awwad; Alhassan, Shikih Hussain; Bukhari, Malath Abdulrahman; Alamri, Abdulrahman Faris; Alamri, Abdulaziz Faris; Alnumari, Abdulaziz Khalafallah; Alsufyani, Nasser Eid; Alhamoud, Abdullah Hassan (International Journal Of Community Medicine And Public Health, 2021)
Tuberculosis is among the oldest endemic conditions affecting humans; however, it remains a significant health issue around the globe. As with previous outbreaks/epidemics, the COVID-19 impact on TB control efforts and outcomes should raise concerns; however, the extent of this impact is currently unknown. In the current study, we aim to review the literature to provide an overview of the available evidence discussing the impact of coronavirus disease-2019 (COVID-19) on TB infections. On one hand, many of the existing reports showed that having TB infection may contribute to developing severe forms of acute respiratory syndrome in patients co-infected with COVID-19, and the presence of underlying TB infection was identified as a risk factor for COVID-19 infection. However, other reports showed that patients with present TB were not more vulnerable to get infected with COVID-19 or to higher mortality rates. In the same context, COVID-19 may have an impact on the late reactivation of TB, which could be mediated through its effects on the immune system functionality and subsequent development of active TB. Moreover, TB preventive treatment programs, awareness campaigns, and anti-TB funding were also affected by COVID-19. Accordingly, the global strategy to end the TB by 2035 may be affected by the COVID-19 pandemic. Hospital admission for TB patients should be restricted to severe cases, to prevent the transmission of COVID-19 in those cases. Due to scarce evidence, more studies are needed to guide management plans in this particular context.